Aktuelle Fotografie aus Österreich : Im Bilde - v obraze. (Wolkersdorf : FLUSS - NÖ Fotoinitiative, 1991)
Aigner, Rolf ; Berger, Walter ; Cibulka, Heinz ; Die Damen ; Dressler, Peter ; Ebenhofer, Walter ; Frey, Magdalena ; Hammerstiel, Robert F. ; Harti, Klaus Dieter ; Hoáková, Tamara ; Maurer, Ewald ; Iglar, Rainer ; Kandl, Leo ; Kempinger, Herwig ; Kowanz, Brigitte ; Kriesche, Richard ; Hoffmann, Peter G. ; Leitner, Paul Albert ; Litschauer, Maria-Theresia ; Matt, Kurt ; Mirtl, Walter K. ; Ponger, Lisl ; Raffesberg, Wolfgang ; Schlegel, Eva ; Schuster, Michael ; Selichar, Günther ; Sodomka, Andrea ; Thormann, Otmar ; Waldl, Robert ; Willmann, Manfred ; Wisniewski, Jana
Aktuelle Fotografie aus Österreich : Im Bilde - v obraze, Kulturinitiative Seebarn 100, FLUSS - NÖ Fotoinitiative, Galerien der Stadt Prag, 1991
boek
Keywords: Oostenrijk